A new pyrano coumarin from Clausena excavata roots displaying dual inhibition against α-glucosidase and free radical. Issue 4 (16th February 2021) - Thant, Tin Myo; Aminah, Nanik Siti; Kristanti, Alfinda Novi; Ramadhan, Rico; Phuwapraisirisan, Preecha; Takaya, Yoshiaki
Abstract: A new pyrano coumarin, identified as excavatin A (1 ) together with two known compounds nordentatin (2 ) and binorpocitrin (3 ) was isolated from the 95% EtOH extract of Clausena excavata . All structures were elucidated by using spectroscopy methods such as extensive NMR and HR-FAB-MS spectrometry. All the isolated compounds were tested on antidiabetes activity by using α-glucosidase inhibition assay and the antioxidant activity by DPPH assay. Compounds 1-3 showed antioxidant activity with IC50 values 0.286, 0.02, 0.278 mM. Among them, 2 exhibited inhibition activity against maltase (IC50 5.45 µM) and sucrase (IC50 43.57 µM). However, compounds (1 ) and (3 ) displayed inhibition on yeast α-glucosidase with IC50 values 1.92 and 5.58 mM.